(untitled) (Modern education and development, 2025)
The article analyzes the application of artificial neural networks in society and its impact in various fields. Artificial neural networks are a technology based on modeling the activity of the human brain and are widely used in analyzing complex data, making decisions, and forecasting. In society, this technology is leading to revolutionary changes in the economy, healthcare, education, transport, everyday life, and other areas. With the help of artificial neural networks, production efficiency increases, medical diagnostics becomes more accurate, education is individualized, and transportation systems operate more efficiently. The article discusses the positive impact of artificial neural networks on society and the ethical and social problems of its development.